Emodin - A natural anthraquinone derivative with diverse pharmacological activities. (October 2021) - Semwal, Ruchi Badoni; Semwal, Deepak Kumar; Combrinck, Sandra; Viljoen, Alvaro
Abstract: Emodin (1, 3, 8-trihydroxy-6-methyl-anthraquinone) is a natural anthraquinone derivative that is present in numerous globally renowned herbal medicines. It is recognised as a protein tyrosine kinase inhibitor and as an anticancer drug, active against various tumour cells, including lung, breast, liver, and ovarian cancer cells. Recently, its role in combination chemotherapy with various allopathic medicines, to minimize their toxicity and to enhance their efficacy, has been studied. The use of emodin in these therapies is gaining popularity, due to fewer associated side effects compared with standard anticancer drugs. Emodin has a broad therapeutic window, and in addition to its antineoplastic activity, it displays anti-ulcer, anti-inflammatory, hepatoprotective, neuroprotective, antimicrobial, muscle relaxant, immunosuppressive and antifibrotic activities, in both in vitro and in vivo models. Although reviews on the anticancer activity of emodin have been published, none coherently unite all the pharmacological properties of emodin, particularly the anti-oxidant, antimicrobial, antidiabetic, immunosuppressive and hepatoprotective activities of the compound. Hence, in this review, all of the available data regarding the pharmacological properties of emodin are explored, with particular emphasis on the modes of action of the molecule. In addition, the manuscript details the occurrence, biosynthesis and chemical synthesis of the compound, as well as its toxic effects on biotic systems. Graphical abstract: Image 1 Highlights: Bioactivity of emodin, a natural anthraquinone, extensively studied. Emodin exhibits anticancer activity via inhibition of protein tyrosine kinases. Emodin is active against many viruses including SARS-CoV. Emodin protects against oxidative damage to DNA, lipids and proteins. Beneficial effects of emodin for diabetes and its complications widely reported.